Rupture After Endovascular Abdominal Aortic Aneurysm Repair: A Multicenter Study. (October 2014) - Antonopoulos, Constantine N.; Kakisis, John D.; Giannakopoulos, Triantafillos G.; Andrikopoulos, Vasilios; Antoniadis, Pavlos; Bessias, Nikolaos; Dervisis, Konstantinos; Georgopoulos, Sotirios; Giannoukas, Athanasios; Kaperonis, Elias; Kiskinis, Dimitrios; Klonaris, Christos; et al.
A total of 22 patients with ruptured abdominal aortic aneurysms (rAAAs) after previous endovascular aortic repair (EVAR; rAAAevar) were presented to 7 referral hospitals in Greece, between January 2006 and April 2012. Type Ia endoleak and endograft migration were identified in 72.7% and 50%, respectively. Compliance to follow-up protocol prior to rupture was 31.8%. In-hospital mortality was 36.4% (9.1% for those treated with secondary EVAR and 63.6% for those treated with open surgical repair, P = .02). An increase in the proportion of patients with rAAAevar among the total number of patients with rAAAs from 1.3% in 2007 to 18.2% in 2012 ( P for trend = .04) was recorded, corresponding to an annual increase of 2.8% (b = 2.84, P = .04). Rupture after EVAR seemed to be a clinical entity encountered with increasing frequency over the past years. Type I endoleak and endograft migration were most frequently observed, whereas compliance to follow-up was low.